Didactic Strategies in Youth and Adult Education in Schools in Alagoas, Brazil. - Castillo-Armijo, P (UNIV LA GRAN COLOMBIA, 2023)
This article aimed to analyze the didactic strategies used by teachers of Youth and Adult Education of three public schools in Alagoas to improve the teaching-learning process. The EJA for many years has been considered an educational subsystem, a poor education for the poor, but there is recognition in recent years of the transformative role it can generate in the lives of people who were excluded from the traditional education system for work reasons, pregnancy, school failure or voluntary dropout. There are also economic reasons that establish the importance of this type of education, being considered as a workforce that must be qualified to enter the increasingly competitive labor market.From a qualitative approach and case study method, research was developed by obtaining data from three focus groups with students and semi-structured interviews with teachers. The data were treated through the content analysis proposed by Bardin (2011). In the speeches arose the dialogic positions of teachers and students object of this research, who demonstrated the importance of the relationship of dialogue and respect between teachers and students of the EJA, highlighting that there are didactic strategies that favor learning, such as practical work and group. However, there is a criticism of the EJA that presents some mechanical processes of nonsense and merely reproductive teaching that do not favor the acquisition of higher thinking skills, such as reflection and analysis of the student s social reality.